2018
DOI: 10.1007/s00402-018-2891-3
|View full text |Cite
|
Sign up to set email alerts
|

Normalized gait analysis parameters are closely related to patient-reported outcome measures after total knee arthroplasty

Abstract: Up till now, only a weak connection could be shown between patient-related outcome measures (PROMs) and measurements obtained by gait analysis (e.g. speed, step length, cadence, ground reaction force, joint moments and ranges of motion) after total knee arthroplasty (TKA). This may result from the methodical problem that regression analyses are performed using data that are not normalized against a healthy population. It does appear reasonable to assume that patients presenting a physiological gait pattern are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…[3] The gait pattern of patients changes dramatically after knee arthroplasty, and a physiological gait pattern after TKA has been shown to lead to better patient-related outcome measures (PROMs), than a non-physiological gait pattern. [4,5] Gait pattern is an important predictor of functional abilities and PROMs after knee arthroplasty and smartphone-based gait analysis Objectives: The aim of this study was to compare the smartphonebased gait analysis data of patients who underwent total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA).Patients and methods: Between January 2016 and April 2019, a total of 51 patients (3 males, 48 females; mean age: 60.92 years; range, 51 to 70 years) who were operated with UKA or TKA in our clinic were retrospectively analyzed. The patients were divided into two groups according to the type of procedure as the UKA group (n=17) and unilateral TKA group (n=34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The gait pattern of patients changes dramatically after knee arthroplasty, and a physiological gait pattern after TKA has been shown to lead to better patient-related outcome measures (PROMs), than a non-physiological gait pattern. [4,5] Gait pattern is an important predictor of functional abilities and PROMs after knee arthroplasty and smartphone-based gait analysis Objectives: The aim of this study was to compare the smartphonebased gait analysis data of patients who underwent total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA).Patients and methods: Between January 2016 and April 2019, a total of 51 patients (3 males, 48 females; mean age: 60.92 years; range, 51 to 70 years) who were operated with UKA or TKA in our clinic were retrospectively analyzed. The patients were divided into two groups according to the type of procedure as the UKA group (n=17) and unilateral TKA group (n=34).…”
mentioning
confidence: 99%
“…[3] The gait pattern of patients changes dramatically after knee arthroplasty, and a physiological gait pattern after TKA has been shown to lead to better patient-related outcome measures (PROMs), than a non-physiological gait pattern. [4,5] Gait pattern is an important predictor of functional abilities and PROMs after knee arthroplasty and smartphone-based gait analysis Objectives: The aim of this study was to compare the smartphonebased gait analysis data of patients who underwent total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA).…”
mentioning
confidence: 99%
“…Dada la importancia de la deambulación en el ser humano y debido a las alteraciones de los patrones de marcha que se producen en los pacientes con secuelas de poliomielitis, los autores del estudio consideran oportuno realizar una caracterización de la cinemática de la marcha en un paciente de estas características. A través del análisis de la información que facilitan estos estudios, es posible generar estrategias en el campo de la rehabilitación de estos pacientes y mejorar la recuperación de la máxima funcionalidad en las actividades de la vida cotidiana (12)(13).…”
Section: Introductionunclassified
“…The presented work takes into account tibiofemoral and patellofemoral kinematics together with soft-tissues to position the implant, with the aim to reproduce native kinematics post-TKA. Restoring native kinematics allows for a more normal gait pattern post-TKA (Blakeney et al, 2019), which may result in improved patient-reported outcome measures (Kirschberg et al, 2018;Biggs et al, 2019). For the specimens studied, the required implant position changes were maximally 2.96 mm and 2.40°.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanics and quality of movement similar to healthy were found to improve post-operative patient-reported outcomes (Kirschberg et al, 2018;Biggs et al, 2019). Musculoskeletal modeling (MSM) allows to investigate the interplay between patient-specific biomechanics, implant alignment and soft tissues (Vanheule et al, 2017).…”
Section: Introductionmentioning
confidence: 99%